"Doctors are in the best position to know…": The perceived medicalization of contraceptive method choice in Ibadan and Kaduna, Nigeria. Issue 8 (August 2016) - Schwandt, Hilary M.; Skinner, Joanna; Saad, Abdulmumin; Cobb, Lisa
Highlights: Contraceptive methods are selected by a doctor using clinical tests. Health professionals are trusted to provide risk-free contraception. Involving clients in contraceptive method choice will likely increase use. Abstract: Objectives: The medicalization and clinic-based distribution of contraceptive methods have been criticized as barriers to increasing levels of contraceptive use in Nigeria and other settings; however, our understanding of how clients themselves perceive the contraceptive method decision-making process is very limited. Methods: Focus group discussions among men and women in Ibadan and Kaduna, Nigeria, were used to examine attitudes and norms surrounding contraceptive method decision-making in September and October of 2010. Results: Choosing a family planning method was presented as a medical decision: best done by a doctor who conducts clinical tests on the client to determine the best, side effect free, contraceptive method for each client. An absolute trust in health professionals, hospitals, and governments to provide safe contraception was evident. Conclusion: The level of medicalization placed on contraceptive method choice by urban Nigerians is problematic, especially since a test that can determine what contraceptive methods will cause side effects in an individual does not exist, and side effects often do occur with contraceptive method use. Practice implications: Provider and client education approaches would help to improve client involvement in contraceptive decision-making and method choice.